DISKRIMINASI GENDER DALAM NOVEL MATA RAISA KARYA ABIDAH EL KHALIEQY KAJIAN FEMINISME - Nurul Safitri; Lili Kasmini; Wahidah Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the existence of gender injustice practices and the strong influence of patriarchal culture in the lives of women, as depicted in the novel Mata Raisa by Abidah El Khalieqy. The novel illustrates how women face discrimination rooted in social norms, cultural values, and family structures that restrict their freedom and mobility. This study aims to describe the forms of gender discrimination, reveal the influence of social norms and patriarchal culture on the lives of female characters, and explain the application of feminist approaches in examining the main character’s resistance to gender injustice. This research employs a descriptive qualitative method using reading and note-taking techniques. The data were analyzed using liberal feminist theory to understand the female character’s struggle to achieve equal rights. The findings indicate that gender discrimination includes restricted mobility, negative labeling of women, the neglect of women’s rights, and social pressures that limit women’s autonomy. Social norms demand that women remain obedient, place them in subordinate positions, and maintain societal control over their behavior and life choices. Patriarchal culture reinforces family rules that position men as dominant, require women to submit to male authority, and limit women’s opportunities in education and public spaces. Through the lens of liberal feminism, the study finds that the character Raisa resists these injustices by pursuing education, expressing her opinions, and making decisions about her own life as a form of struggle toward achieving equal rights